PENYELESAIAN SENGKETA ANTARA PT. ASH – SHAHABBAH DENGAN KONSUMEN TENTANG PEMBELIAN SUSU HERBAL OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN DI BUKITTINGGI - Mardius, Mhd Aidil Nurrahman dan (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
That this dispute resolution is resolved by means of mediation mediated by BPSK Bukittinggi, in the mediation process producers are considered less cooperative and reject some of the demands made by consumers, causing several obstacles. Obstacles that occurred in the form of the prosusen refusing to carry out laboratory tests, refusing claims for compensation and not complying with Law No. 8 of 1999 in Article 7 related to the obligations of business actors. And after mediation again, finally both parties agreed to make peace with several agreements. which must be obeyed by both parties and the results of the peace are contained in the BPSK Bukittinggi decision letter. The decision was made on Tuesday, February 11, 2020 with the number 03/P/2020/BPSK – BKT by adjudicating the decision which reads: ratify the deed of peace between the applicant and the termosin and punish both parties to comply with the contents of the agreed agreement.